Assessment of University Campus Cycling Facilities: the Studentsâ€™ Perceptions - Khairunisa Zainal, Siti; Nazri Borhan, Muhamad; Nazrul Hakimi Ibrahim, Ahmad; Mohd Iznan Tuan Yaakub, Nik; Razuhanafi Mat Yazid, Muhamad (International Journal of Engineering and Technology, 2019)
Cycling can prevent environmental pollution, such as air pollution and noise pollution. The use of motorised mode of transportation in campus will be more exposed to dangers of pollution, such as carbon monoxide. This study aims to measure and identify factors that contribute to students' perceptions and satisfaction levels of cycling facilities. Factors that were studied can further improve the existing facilities. Efficiency and effectiveness can be observed in service quality or facilities provided by relevant parties. This study focuses on male and female students who always cycle in the National University of Malaysia (UKM) and involves the participation of students from Year 1 to Year 4. A total of 200 questionnaires were distributed to these students. From the Importance-Performance Analysis (IPA) factors, such as cycling lane good surface conditions (sidewalk), clean environment and willingness to cycle should be considered because these factors contribute to customer satisfaction.Â Â